Unsur Intrinsik Dalam Naskah Drama “Trik“ Karya Putu Wijaya - Ine Patmawati; Euis Winda Nengsih; Fatin Salsa Nabila (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Putu Wijaya's Trik Drama is one of the representations of the absurd theater style that developed in Indonesia. This work depicts a critique of social, political, and cultural conditions, where life is often full of manipulation, falsehood, and power play. As a prolific writer, Putu Wijaya uses this script to highlight the complexity of human life in the face of a reality that is full of uncertainty and conflict. In the context of history and culture, Trik emerged as a response to the social situation in Indonesia which was full of power dynamics and manipulation during the New Order period. Through absurd symbols and profound dialogue, this text pokes fun at human behavior that often uses tricks or deception to achieve personal ends, without considering moral values or truth. As part of modern Indonesian literature, Trik also reflects Putu Wijaya's view of art as a medium to arouse public awareness. With a unique theatrical approach, he encourages the audience or readers to think critically about the issues that humans face in daily life. This manuscript is not only relevant in its time, but also remains actual in describing the ethical and existential dilemmas of human beings to this day. Putu Wijaya's Drama Trik is an absurd theatrical work that explores the themes of manipulation, power, and the search for truth in human life. The abstract of the play includes the conflict between reality and illusion constructed by the characters, where they utilize each other's tricks and deceptions to achieve personal goals. In this drama, Putu Wijaya criticizes human nature that is often caught up in a game of power, lies, and boundless ambition. With a distinctive writing style and full of irony, Trik invites readers or viewers to reflect on the essence of truth, integrity, and existence in a life full of uncertainty.